Pedigree based DNA sequencing pipeline for germline genomes of cancer families - Försti, Asta; Kumar, Abhishek; Paramasivam, Nagarajan; Schlesner, Matthias; Catalano, Calogerina; Dymerska, Dagmara; Lubinski, Jan; Eils, Roland; Hemminki, Kari (Hereditary cancer in clinical practice, 2016)
In the course of our whole-genome sequencing efforts, we have developed a pipeline for analyzing germline genomes from Mendelian types of cancer pedigrees (familial cancer variant prioritization pipeline, FCVPP).